Bullying Risk Survey in Elementary Schools - Aqielasyifa, Qaireen; Mulyani, Winda Nur; Siswanto, Joko (Yayasan Rumah Ilmu Professor, 2023)
This study aims to determine the act of bullying and how to prevent it at SAI Palembang. This research uses quantitative descriptive research with a survey approach. This research was conducted by conducting observations using questionnaires, interviews, and documentation conducted at SAI Palembang in September 2022-February 2023. The questionnaire used is a list of 8 questions and observation there are 14 questions that have been tested previously on other students. The sample of this study was 18 SAI Palembang students from grades 3-6. The data analysis used was descriptive statistical analysis with data presentation using the percentage of bullying actions. Bullying carried out by students, namely mocking and hitting, which is 83%, and the smallest percentage is that the treatment is carried out repeatedly, which is 22%. From the results of the questionnaire on 18 students in grades 3 to 6, it can be concluded that indications of bullying actions exist in SAI Palembang, but this cannot be said to be a bullying incident because the main characteristics of bullying in the form of actions carried out intentionally by someone on another person repeatedly were not found. Bullying is disruptive in nature to other people because of the impact of negative behavior which is now popular among society, causing discomfort to other people or victims of bullying. Knowing the factors that support bullying behavior needs to be considered.